Cr-Fe KOADSORPSI BY KITOSAN - Endang Widjajanti; AK Prodjosantoso (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2008)
This study aims to determine the ability of adsorption of chitosan on Cr (III) and Fe (III) ions simultaneously in various concentration variations. As research subject is chitosan isolated from crab shells and made through three stages namely deproteination stage, demineralisasi and deasetilasi. As the object of research is the adsorption power of chitosan against Cr (III) and Fe (III) metal ions, both for each ion and simultaneously. The adsorption process using a batch system is carried out for 24 hours at room temperature under optimum pH system conditions with a 1: 100 (w / v) adsorbent ratio at concentrations of 100 ppm to 1000 ppm. Chitosan adsorption is the ratio between the amount of metal ions adsorbed per gram of chitosan, adsorbat concentration is determined using Atomic Absorption Spectrophotometer The results showed that the adsorption capacity of chitosan on Fe (III) was stronger than Cr (III) in both single adsorption and simultaneous adsorption, and the process was classified as coadsorption.